Age Related Histomorphological Changes in Cerebral Neocortex of Pig (Sus scrofa) - Sujana, K.M. (Indian Journal of Veterinary Anatomy, 2020)
The present study was conducted on histomorphological aspects of cerebral neocortex of Large White Yorkshire crossbred pigs. The cerebral neocortex was consisted of six layers from superficial to deep viz., the molecular layer, external granular layer, external pyramidal layer, internal granular layer, internal pyramidal layer and fusiform layer. All these layers were composed of neuronal cells, glial cells, neuropil and blood vessels. The number of neuronal cells decreased, while the number of glial cells and amount of neuropil was increased from preweaner to finisher age group. The lipofuscin pigment was accumulated in neuronal cells, particularly in Betz cells and it was increased with age. The neocortical width was significantly increased from preweaner to grower age group and slightly decreased from grower to finisher age group.